Adaptive current differential protection for active distribution networks accommodating high levels of PV integration - CHEN Shuiyao; XU Feng; PAN Wulue; LI Yuehui; WU Jizeng; LIU Sumei (Zhejiang dianli)
The large-scale integration of photovoltaic （PV） sources into distribution networks alters the differential current and braking current of line differential protection， leading to a risk of maloperation in traditional ratio restraint differential protection. This study analyzes the changes in the fundamental-frequency current amplitude and phase angle on both sides of the line connected to the PV source， highlighting the subsequent issues with traditional current differential protection. By deriving the mathematical relationship between the ratio restraint coefficient and the phase angles of the currents on either side， as reflected in the critical operation curve of differential protection， the paper proposes an improved adaptive current differential protection criterion for adjusting the ratio restraint coefficient. A simulation model of distribution networks with PV stations is developed using PSCAD/EMTDC to test the proposed protection strategy， demonstrating its effectiveness and reliability under high levels of PV integration.